Characterization of a Functionally Unknown Arginine–Aspartate–Aspartate Family Protein From Halobacillus andaensis and Functional Analysis of Its Conserved Arginine/Aspartate Residues - Shao, Li; Abdel-Motaal, Heba; Chen, Jin; Chen, Huiwen; Xu, Tong; Meng, Lin; Zhang, Zhenglai; Meng, Fankui; Jiang, Juquan (Frontiers in Microbiology, 2018)
Arginine-aspartate-aspartate (RDD) family representing a category of transmembrane proteins containing one highly conserved arginine and two highly conserved aspartates has been functionally uncharacterized as yet. Here we present the characterization of a member of this family designated RDD from the moderate halophile Halobacillus andaensis NEAU-ST10-40T and report for the first time that RDD should function as a novel Na+(Li+, K+)/H+ antiporter. It's more interesting whether the highly conserved arginine/aspartate residues among the whole family or between RDD and its selected homologs are related to the protein function. Therefore, we analyzed their roles in the cation-transporting activity through site-directed mutagenesis and found that D154, R124, R129 and D158 are indispensable for Na+(Li+, K+)/H+ antiport activity whereas neither R35 nor D42 is involved in Na+(Li+, K+)/H+ antiport activity. As a dual representative of Na+(Li+, K+)/H+ antiporters and RDD family proteins, the characterization of RDD and analysis of its important residues will positively contribute to the knowledge of the cation-transporting mechanisms of this novel antiporter and the roles of highly conserved arginine/aspartate residues in the functions of RDD family proteins.